Decentralization of wage determination: Evidence from a national teacher reform - Alexander Willén (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2019)
Despite a global trend of wage decentralization over the past 30 years, we know very little about the labor market implications of decentralized wage determination. A main reason is the lack of exogenous variation in wage regulation linked to detailed outcome data. Using Swedish registry data and exploiting a reform that replaced the fixed national pay scale for teachers with individual wage bargaining, I overcome these issues and provide new evidence on the labor market effects of wage decentralization. The paper presents three sets of empirical results. First, I show that the reform significantly changed the wage structure of teachers. Second, I demonstrate that these wage changes did not affect teacher composition or student outcomes. Finally, I find support for a wage spillover effect to substitute occupations, providing evidence on the dynamics of wage determination across occupations. I argue that the wage spillover effect coupled with the compressed Swedish wage structure likely explains the lack of effects on teacher and student outcomes.
Keywords: I20; I28; J31; J45; 330; Wage Regulation; Decentralization; Teacher Labor Market